2015
DOI: 10.1590/0104-07072015001362014
|View full text |Cite
|
Sign up to set email alerts
|

The production of knowledge in nursing in the BRIC countries: a bibliometric study

Abstract: The electronic databases and tools for promoting knowledge make scientific and technological development possible in the areas of health and of nursing. This bibliometric study aimed to map the indicators regarding nursing, published in 2012, in the SJR database, by the BRIC countries. These countries' production in nursing was analyzed comparatively in relation to documents, citations, h-index and international collaboration. The results show: 1,039 articles published in Brazil, nine articles published in Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, India outperformed other BRIC countries with higher citation impact. Santiago and Carlantonio (2015) analyzed the scientific production of knowledge in the field of nursing in the BRIC countries in relation to documents, citations, h-index and international collaboration. They found that Brazil had higher citation impact in terms of quality among the BRIC countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, India outperformed other BRIC countries with higher citation impact. Santiago and Carlantonio (2015) analyzed the scientific production of knowledge in the field of nursing in the BRIC countries in relation to documents, citations, h-index and international collaboration. They found that Brazil had higher citation impact in terms of quality among the BRIC countries.…”
Section: Literature Reviewmentioning
confidence: 99%